Quality of canine epididymal spermatozoa during storage at 4ï°C - Setiadi, M.A; ., Yulnawati; Suprayogi, A (Indonesian Animal Sciences Society, 2007)
The aim of this present study was to investigate the quality of canine epididymal spermatozoa during storage at 4°C. Spermatozoa was collected by flushing technique with physiological saline (NaCl 0.9% w/v) and diluted in modified Tris based extender containing 20% (v/v) of egg yolk for three days. The result showed that mean concentration of spermatozoa from cauda epididymal was 95.29.106 spz/ml. The percentage of progressive motility and membrane integrity of spermatozoa on time of collection was 70.71% and 72.85%, respectively. Quality of epididymal spermatozoa was decreased significantly (P<0,05) during storage at 4°C. The percentage of progressive motility during storage were 70.71% on day 0 (H-0, after diluted), 60.71% (H-1), 45.71% (H-2), and 33.57% (H-3). The percentage of membrane integrity during storage were 72.85, 68.88, 61.06 and 47.47% on H-0, H-1, H-2 and H-3, respectivelly. In conclusion, quality of canine epididymal spermatozoa was decreased during three days of storage at 4°C. Key Words: Epididymal Sperm, Storage, Canine